Tryptophan and Biogenic Amines in the Differentiation and Quality of Honey - Borges, Cristine Vanz; Nunes, Aline; Costa, Vladimir Eliodoro [UNESP]; Orsi, Ricardo de Oliveira [UNESP]; Basilio, Leticia Silva Pereira [UNESP]; Monteiro, Gean Charles [UNESP]; Maraschin, Marcelo; Lima, Giuseppina Pace Pereira [UNESP] (SAGE Publications, 2022)
Honey is a natural product with beneficial properties to health and has different characteristics depending on the region of production and collection, flowering, and climate. The presence of precursor amino acids of- and biogenic amines can be important in metabolomic studies of differentiation and quality of honey. We analyzed 65 honeys from 11 distinct regions of the State of Santa Catarina (Brazil) as to the profile of amino acids and biogenic amines by HPLC. The highest L-tryptophan (Trp), 5-hydroxytryptophan (5-OH-Trp), and tryptamine (Tryp) levels were detected in Cfb climate and harvested in 2019. Although we have found high content of serotonin, dopamine, and L-dopa in Cfb climate, the highest values occurred in honey produced during the summer 2018 and at altitudes above 900 m. Results indicate that the amino acids and biogenic amine levels in honeys are good indicators of origin. These data warrant further investigation on the honey as source of amino acids precursor of serotonin, melatonin, and dopamine, what can guide the choice of food as source of neurotransmitters.
Keywords: dopamine; L-dopa; L-tryptophan; melatonin; serotonin